Circulating tumor cells as a predictive biomarker in patients with small cell lung cancer undergoing chemotherapy. (October 2017) - Aggarwal, Charu; Wang, Xingmei; Ranganathan, Anjana; Torigian, Drew; Troxel, Andrea; Evans, Tracey; Cohen, Roger B.; Vaidya, Bhavesh; Rao, Chandra; Connelly, Mark; Vachani, Anil; Langer, Corey; et al.
Highlights: CTCs are detectable at baseline in SCLC and correlate with stage and outcomes. CTCs were measured at baseline, prior to each chemotherapy cycle, and at relapse. CTCs added independent prognostic information for patients undergoing chemotherapy. The first trial to prospectively evaluate markers of both DNA damage and apoptosis on CTC. We show that assessment of these biomarkers on CTCs was feasible. Abstract: Background: There are no biomarkers for assessment of disease burden or activity of therapy in SCLC. Patients and methods: We conducted a prospective study enumerating serial CTCs in patients with newly diagnosed limited disease (LD) and extensive stage (ED) SCLC. CTCs demonstrating DNA damage and apoptosis based on γH2AX and M30 staining were also assessed. We correlated CTC number with disease stage, survival outcomes and tumor burden by RECIST. Results: Between 03/2011-10/2013, 50 evaluable patients were enrolled (20 LD). Baseline CTC number was higher for ED (median CTC 71 vs. 1.5 for LD; p 0.0004 ). Patients with <5 CTC had longer PFS but not OS (11 vs. 6.7 months, p 0.0259 and 15.5 vs. 12.9 months, p 0.4357 ). A higher cutoff (CTC < 50 or CTC ≥ 50) was significantly correlated with both OS (20.2 vs. 11.8 months, p 0.0116 ) and PFS (10 vs. 4.8 months, p 0.0002 ). Patients with <5 CTC on day 1 of cycle 2 had longer PFS (10 vs. 3.17 months, p < 0.001) and OS (18 vs. 9 months, p 0.0001 ). Patients with an increase in γ2HAX-positive CTCs after chemotherapy had longer OS compared to patients without an increase (25.3 vs. 9 months, p 0.15 ). Conclusions: This study demonstrates that CTCs at baseline and Cycle 2 of chemotherapy correlate with disease stage and survival in patients with SCLC, suggesting that CTCs may be used as a surrogate biomarker for clinical response. Confirmatory prospective clinical trials are needed before we can incorporate routine evaluation of CTCs into clinical practice.